Developing an Arabic Language Community Program to Enhance the Language Environment for Female Students - Ali, Himmatul Choiroh; Farid, Edi Kurniawan; Sofa, Ainur Rofiq (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
Purpose This study aims to develop an Arabic Language Community Program to enhance the Arabic language environment among female students. The program was developed in response to the need for a supportive language environment that enables students to use Arabic actively and consistently in their daily communication. Design/Methodology/Approach This study employed the Research and Development (R&D) method to develop an Arabic Language Community Program. The research involved 20 female students, Arabic language teachers, and dormitory supervisors at Nuriddahlani Islamic Boarding School for Girls. The participants were selected using purposive sampling, with one student representing each group participating in the interview to identify learners' needs. Data were collected through observations, interviews, questionnaires, and document analysis and were analyzed using a descriptive qualitative approach. Based on the needs analysis, the program was developed through the design of structured language activities, including daily vocabulary habituation, daily Arabic conversations, group discussions, public speaking (khiṭābah), language competitions, and continuous monitoring and evaluation. Findings The findings revealed that students need a structured language program that supports continuous Arabic language practice. The main needs identified include improving speaking skills, expanding opportunities to use Arabic in daily life, providing interactive language activities, and establishing a systematic monitoring and evaluation process. Based on these findings, an Arabic Language Community Program was developed to create a sustainable Arabic language environment that encourages students to use Arabic more confidently and consistently. Research Limitations/Implications This study focused on developing an Arabic Language Community Program based on a needs analysis and did not evaluate its effectiveness through field implementation. The findings suggest that the proposed program can serve as a practical model for strengthening the Arabic language environment and enhancing students’ communicative competence in Islamic educational institutions. Future research should implement the program and evaluate its effectiveness in improving students’ Arabic language proficiency.